Tingkat Kecemasan Wasit Indonesia Saat Memimpin Pertandingan Sepak Bola - Nufi Saidatus Tsaniyah; Nurhadi; Thoriq Munir Alkatiri; Anung Priambodo; Achmad Widodo (Indonesian Journal of Kinanthropology (IJOK), 2025)
Background: Football is a highly popular sport worldwide, including in Indonesia. In football matches, referees play a crucial role that significantly determines the course of the game and its final outcome. However, this role often leads to pressure that can trigger anxiety due to physical, mental, and emotional demands from various parties such as players, coaches, and spectators. This study aims to analyze the level of anxiety experienced by Indonesian football referees when officiating professional matches. Methods: This study uses a descriptive quantitative approach with surveys as the data collection method. The research sample consists of 21 professional football referees in Indonesia, aged 25-40 years, with 1-18 years of experience. The research instrument used is the Football Referee Anxiety Scale (FRAS) questionnaire, covering four dimensions of anxiety: cognitive, affective, somatic, and motoric. Results: The study results show that the majority of referees have a low level of anxiety, with an average score of 67.19. A total of 52.4% of referees have low anxiety, while 33.3% fall into the high category. The most prominent aspects of anxiety are cognitive and affective dimensions, where several referees experience difficulties in decision-making and emotional burdens Conclusions: The level of anxiety among Indonesian football referees when officiating professional matches varies. Most referees have a low level of anxiety. The most frequently affected aspects of anxiety include the cognitive and affective dimensions, which involve feelings of worry, difficulty concentrating, and emotional burdens. Keywords: anxiety; referee anxiety; football referee